Newly diagnosed diabetes is associated with a higher risk of mortality than known diabetes in hospitalized patients with COVID‐19. Issue 10 (30th June 2020) - Li, Huiqing; Tian, Shenghua; Chen, Ting; Cui, Zhenhai; Shi, Ningjie; Zhong, Xueyu; Qiu, Kangli; Zhang, Jiaoyue; Zeng, Tianshu; Chen, Lulu; Zheng, Juan
Abstract: Aim: To evaluate the association between different degrees of hyperglycaemia and the risk of all‐cause mortality among hospitalized patients with COVID‐19. Materials and Methods: In a retrospective study conducted from 22 January to 17 March 2020, 453 patients were admitted to Union Hospital in Wuhan, China, with laboratory‐confirmed severe acute respiratory syndrome coronavirus 2 infection. Patients were classified into four categories: normal glucose, hyperglycaemia (fasting glucose 5.6‐6.9 mmol/L and/or HbA1c 5.7%‐6.4%), newly diagnosed diabetes (fasting glucose ≥7 mmol/L and/or HbA1c ≥6.5%) and known diabetes. The major outcomes included in‐hospital mortality, intensive care unit (ICU) admission and invasive mechanical ventilation (IMV). Results: Patients with newly diagnosed diabetes constituted the highest percentage to be admitted to the ICU (11.7%) and require IMV (11.7%), followed by patients with known diabetes (4.1%; 9.2%) and patients with hyperglycaemia (6.2%; 4.7%), compared with patients with normal glucose (1.5%; 2.3%), respectively. The multivariable‐adjusted hazard ratios of mortality among COVID‐19 patients with normal glucose, hyperglycaemia, newly diagnosed diabetes and known diabetes were 1.00, 3.29 (95% confidence interval [CI] 0.65‐16.6), 9.42 (95% CI 2.18‐40.7) and 4.63 (95% CI 1.02‐21.0), respectively. Conclusion: We showed that COVID‐19 patients with newly diagnosed diabetes had the highest risk of all‐cause mortality compared with COVID‐19 patients with known diabetes, hyperglycaemia and normal glucose. Patients with COVID‐19 need to be kept under surveillance for blood glucose screening.